Diverse values of nature for sustainability - Pascual, Unai; Balvanera, Patricia; Anderson, Christopher B.; Chaplin-Kramer, Rebecca; Christie, Michael; Gonzalez-Jimenez, David; Martin, Adrian; Raymond, Christopher M.; Termansen, Mette; Vatn, Arild; Athayde, Simone; Baptiste, Brigitte; et al. (My University, 2023)
Twenty-five years since foundational publications on valuing ecosystem services for human well-being(1,2), addressing the global biodiversity crisis(3) still implies confronting barriers to incorporating nature's diverse values into decision-making. These barriers include powerful interests supported by current norms and legal rules such as property rights, which determine whose values and which values of nature are acted on. A better understanding of how and why nature is (under)valued is more urgent than ever(4). Notwithstanding agreements to incorporate nature's values into actions, including the Kunming-Montreal Global Biodiversity Framework (GBF)(5) and the UN Sustainable Development Goals(6), predominant environmental and development policies still prioritize a subset of values, particularly those linked to markets, and ignore other ways people relate to and benefit from nature(7). Arguably, a 'values crisis' underpins the intertwined crises of biodiversity loss and climate change(8), pandemic emergence(9) and socio-environmental injustices(10). On the basis of more than 50,000 scientific publications, policy documents and Indigenous and local knowledge sources, the Intergovernmental Platform on Biodiversity and Ecosystem Services (IPBES) assessed knowledge on nature's diverse values and valuation methods to gain insights into their role in policymaking and fuller integration into decisions(7,11). Applying this evidence, combinations of values-centred approaches are proposed to improve valuation and address barriers to uptake, ultimately leveraging transformative changes towards more just (that is, fair treatment of people and nature, including inter- and intragenerational equity) and sustainable futures.
Keywords: Equity; Transformative Learning